Integrated Marketing Communications (IMC) As A Model And Its Application: An Exploratory Study In Malaysia. - Noor, Shuhaida Md (2004)
A topic of growing interest in marketing communications is Integrated Marketing Communications (IMC). It is the philosophy and practice of systematically coordinating a brand's marketing communications elements, both through planned and unplanned messages. IMC is believed to be able to provide a better management of the traditional promotional mix as well as an improved management of customer contact points, thus bringing greater return on investment for a company's marketing communications activities.